The effects of advanced glycation end products (AGEs) on dermal wound healing and scar formation: a systematic review - Lennert Van Putte; Sofie De Schrijver; Peter Moortgat (SAGE Publishing, 2016)
Introduction: With ageing, the skin gradually loses its youthful appearance and functions like wound healing and scar formation. The pathophysiological theory of Advanced Glycation End products (AGEs) has gained traction during the last decade. This review aims to document the influence of AGEs on the mechanical and physiologic properties of the skin, how they affect dermal wound healing and scar formation in high-AGE populations like elderly patients and diabetics, and potential therapeutic strategies. Methods: This systematic literature study involved a structured search in Pubmed and Web of Science with qualitative analysis of 14 articles after a three-staged selection process with the use of in- and exclusion criteria. Results: Overall, AGEs cause shortened, thinned, and disorganized collagen fibrils, consequently reducing elasticity and skin/scar thickness with increased contraction and delayed wound closure. Documented therapeutic strategies include dietary AGE restriction, sRAGE decoy receptors, aminoguanidine, RAGE-blocking antibodies, targeted therapy, thymosin β4, anti-oxidant agents and gold nanoparticles, ethyl pyruvate, Gal-3 manipulation and metformin. Discussion: With lack of evidence concerning scars, no definitive conclusions can yet be made about the role of AGEs on possible appearance or function of scar tissue. However, all results suggest that scars tend to be more rigid and contractile with persistent redness and reduced tendency towards hypertrophy as AGEs accumulate. Conclusion: Abundant evidence supports the pathologic role of AGEs in ageing and dermal wound healing and the effectiveness of possible therapeutic agents. More research is required to conclude its role in scar formation and scar therapy.